Penatalaksanaan Fisioterapi Pada Tuberkulosis Paru Di Rumah Sakit Paru Ario Wirawan Salatiga - Meidania, Monalisa, Isnaini Herawati S.Fis., Ftr., M.Sc (2015)
Background: TB (Tuberculosis) is a disease caused by the bacterium Mycobacterium Tuberculosis and seven related mycobacterial species such as Mycobacterium bovis, Mycobacterium africanum, Mycobacterium tuberculosis Canetti and mungi. Pulmonary tuberculosis is a disease caused by tuberculosis Myobacterium, namely aerobic bacteria that can live mainly in the lungs or in various other bodies that have a high oxygen partial pressure. Aims of Research: To study about physiotherapy managementin the case of tuberculosisin reducing shortness of breath, reduce spasms in the accessories respiratory muscle, reduce chest pain, improvedthoracic expansion and clear the airway with modalities IR (Infra red) and ACBT (Active Cycle of Breathing Technique). Results:After terapy for about three times the obtained results of the assessment ofshortness of breath T0 : 5to T3 : 4, motion pain T0 : 2, to T3 : 0, no decrease spasms in the accessories respiratory muscle, no increase thoracic expansion, airway to sound crackles. Conclusion: IR(Infra red)can reduce motion pain when retraksi and protaksi,has not decrease spasms in them.sternocleidomastoideusright and left, andACBT(Active Cycle Breathing Technique)can reduceshortness of breath, has not effectively improve thoracic expansion and has not effectively clear the airway. Key words: active cycle breathing technique(ACBT),breathing control (BC), deep breathing, forced expiration technique(FET), infra red (IR), thoracicexpansion exercise(TEE), tuberkulosis (TB).